Does hepatotoxicity interfere with endocrine activity in zebrafish (Danio rerio)?. (January 2020) - Baumann, Lisa; Holbech, Henrik; Schmidt-Posthaus, Heike; Moissl, Angela P.; Hennies, Mark; Tiedemann, Janina; Weltje, Lennart; Segner, Helmut; Braunbeck, Thomas
Abstract: Vitellogenin (VTG), a well-established biomarker for the diagnosis of endocrine activity in fish, is used in multiple OECD test guidelines (TG) to identify activities of chemicals on hormonal pathways. However, the synthesis of VTG may not only be modified by typical endocrine-related pathways, but also through non-endocrine-mediated processes. In particular, hepatotoxicity, i.e. toxicant-induced impairment of liver structure and function, might influence VTG as a biomarker, since VTG is synthesized in hepatocytes. An intimate understanding of the interplay between endocrine-related and non-endocrine-related pathways influencing VTG production is crucial for the avoidance of erroneous diagnoses in hazard assessment for regulatory purposes of chemical compounds. In order to investigate whether hepatotoxicity may interfere with hepatic VTG synthesis, adult zebrafish ( Danio rerio ) were exposed to three well-known hepatotoxicants, acetaminophen, isoniazid and acetylsalicylic acid, according to OECD TG 230. Various hepatotoxicity- and endocrine system-related endpoints were recorded: mRNA expression of selected endocrine- and hepatotoxicity-related marker genes in the liver; VTG levels in head/tail homogenates; and liver histopathology. All three test compounds induced significant, but mild single cell necrosis of hepatocytes and transcriptional changes of hepatotoxicity-related marker genes, thus confirming hepatotoxic effects. A positive correlation between hepatotoxicity and reduced hepatic VTG synthesis was not observed, with the single exception of a weak increase in female zebrafish exposed to APAP. This suggests that – in studies conducted according to OECD TG 229 or 230 − it is unlikely that hepatotoxic chemicals will interfere with the hepatic capacity for VTG synthesis. Highlights: Vitellogenin synthesis in fish liver might be influenced by hepatotoxicants. Adult zebrafish were exposed to 3 well-known hepatotoxicants. Histopathology and liver marker gene expression confirmed impact on liver. Only one hepatotoxicant induced mild vitellogenin level changes. Interference of hepatotoxicity with endocrine activity cannot be confirmed.